Peningkatan Kreativitas melalui Pelatihan Microsoft Word dan PowerPoint kepada Siswa XI IPA Madrasah Aliyah Pekanbaru - Oni Sawitri; Destia Destia; Neng Solihat; Yuli Amalia (Lembaga Pengembangan Kinerja Dosen, 2025)
Student creativity in processing information and presenting it interestingly is an important skill in the world of modern education. This service aims to increase the creativity of class XI Science students at Madrasah Aliyah Pekanbaru through training in the use of Microsoft Word and Microsoft PowerPoint. This training includes the delivery of material and direct practice. This training provides an in-depth understanding of the features of these two applications, such as text processing, presentation design, and the function and use of CTRL A-Z in Microsoft Word. This training contributes to developing students' creativity while increasing their readiness to face academic and professional challenges in the future.